THE URGENCY OF ARCHIVISTS AS PROFESSIONALS IN AUTOMATION-BASED ARCHIVES MANAGEMENT - Ningrum, Aisyah Wahyu Kusuma (PERSPEKTIF: Journal of Social and Library Science, 2024)
The purpose of this study is to identify and explain the urgency of archivists as professionals who manage archives based on automation. The type of research used is qualitative research which is a literature study using books and other literatures as the main object of this research. In library research, the method used to collect research data is in the form of library data that has been selected, searched, presented and analyzed so that the data presented is in the form of words that are processed to be concise and systematic. The data analysis technique used is a content analysis technique which is a scientific analysis of the essence of a data. The results obtained through this research are that as professional staff, archivists have a very important urgency in automation-based archive management because without competent archivists, automation-based archive management will not be able to run properly. The benefit of carrying out this research is that each agency can further improve the quality of archive management through an automation system with managers who are truly experts in their fields or professional archivists, both archivists who are graduates from universities and archivists who have attended various training/training so that the quality of archive management in These agencies are increasing.